1G to 5G Mobile Network in Indonesia - Nursyahman, Irsan Aulia; Muhammad Rayhan Baras; Maisya Farah; Reby Jovanza Guestfint; Ishmah Rusdianti (Indonesian Journal of Electrical Engineering and Electronics, 2024)
The rapid development of mobile communication technology, from the first generation (1G) to the fifth generation (5G), reflects not only global technological advancements but also adaptations to local needs and unique infrastructural challenges in Indonesia. This paper provides a comprehensive review of the evolution of mobile network technologies from 1G to 5G, focusing particularly on their implementation and impact in Indonesia. The advent of 5G marks a significant milestone worldwide, including in Indonesia, bringing profound changes in how people access and utilize communication technologies. Understanding this technological journey is increasingly relevant, considering its potential to drive innovation across various sectors such as healthcare, education, and industry. Hence, grasping the progression from 1G to 5G is essential not only for technology professionals but also for the general public who will directly experience these advancements.